2018
DOI: 10.1007/s00590-018-2195-x
|View full text |Cite
|
Sign up to set email alerts
|

Lower back and neck pain among dentistry students: a cross-sectional study in dentistry students in Northern Greece

Abstract: Our findings indicate that among dentistry students appears to be a causative relationship between their professional activities and the experienced spinal pain. These findings may be useful in a possible future restructuring of the educational program in dental schools, as well as in improving the ergonomics of dentistry working units.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 14 publications
1
19
0
Order By: Relevance
“…It has been reported that low back pain usually occurs within the first 5 years of professional life. [5][6][7][8] In our study, we observed that low back pain occurred approximately 7.05 years after starting to perform rhinoplasty operations.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…It has been reported that low back pain usually occurs within the first 5 years of professional life. [5][6][7][8] In our study, we observed that low back pain occurred approximately 7.05 years after starting to perform rhinoplasty operations.…”
Section: Discussionmentioning
confidence: 74%
“…Maintaining a certain posture for a long time while working is dependent on permanent muscle loading. [5][6][7][8][9] Muscle loading that occurs to maintain this working position causes fatigue and decreases muscle strength. This posture is directly related to the person's mechanical competence and physiological functions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regardless of how qualitative the methodology of current studies are; the fact remains, study after study has shown that dental care providers are at a high risk for developing occupational cumulative trauma. 1,3,4,[6][7][8][9] The variety of MSDs impacting dental health professionals is diverse and often linked directly to the nature of the occupational tasks completed. Dental hygienists and dental assistants report greater frequency of upper back, neck, and shoulder pain.…”
Section: Introductionmentioning
confidence: 99%
“…The acquisition of incorrect and vicious static postures assumed early in a sitting posture to write on school furniture can damage the curvature of the spine in children and adolescents, because in this period, the locomotor system is in the process of adjusting and maturing [5,6]. In addition, staying in a prolonged seated posture a day can trigger postural imbalance as well as increase the pressure between the intervertebral discs, bringing future risks and damage to the spine [7].…”
Section: Introductionmentioning
confidence: 99%